Structured education program improves the coping with atopic dermatitis in children and their parents: a multicenter, randomized controlled trial - Kupfer, Jörg; Gieler, Uwe; Diepgen, Thomas L.; Fartasch, Manigé; Lob-Corzilius, Thomas; Ring, Johannes; Scheewe, Sibylle; Scheidt, Reginald; Schnopp, Christina; Szczepanski, Rüdiger; Staab, Doris; Werfel, Thomas; et al. (Journal of psychosomatic research, 2010)
Objective - The objective of this study was to prove training-specific effects in children with atopic dermatitis (AD) and their parents concerning coping with the disease after their participation in a training program. In the 1-year follow-up, the changes in the training group were compared to the changes in a waiting control group while controlling the effects of the changes in severity scores. - Methods - One hundred eighty-five children aged 8-12 years and their parents participated in the study. Complete data sets at the 1-year follow-up were available for 185 parent-child pairs (102 training group; 83 waiting control group). In addition to the severity of the AD [measured with the Scoring Atopic Dermatitis (SCORAD)], data on children's itching-scratching cognitions and coping behavior and on parents handling their affected children were used in the analysis. To study whether the intervention group experienced an additional psychological benefit, which is not due to the SCORAD values, analyses of covariance with repeated measures with standardized residual change scores of the SCORAD as covariate were calculated. - Results - The intervention group showed greater improvement in children's coping behavior and in parents' handling their affected children. Additional effects of the training program not due to somatic improvement could be seen in the scales of itching-scratching cognitions and in three of four scales on parents dealing with their affected children. - Conclusion - The training program, which was tested in the German Atopic Dermatitis Intervention Study, had effects on almost all explored psychological variables. Therefore, additional psychological benefit in the training group does not only depend on the greater improvement of SCORAD values in this group.